Unraveling the reaction mechanisms of electrode materials for sodium‐ion and potassium‐ion batteries by in situ transmission electron microscopy. Issue 2 (22nd February 2022) - Wang, Hong; Liu, Fang; Yu, Ruohan; Wu, Jinsong
Abstract: Sodium ion batteries (SIBs) and potassium ion batteries (PIBs) have caught numerous attention due to the low cost and abundant availability of sodium and potassium. However, their power density, cycling stability and safety need further improvement for practical applications. Investigations on the reaction mechanisms and structural degradation when cycling are of great importance. In situ transmission electron microscopy (TEM) is one of the most significant techniques to understand and monitor electrochemical processes at an atomic scale with real‐time imaging. In this review, the current progress in unraveling reaction mechanisms of electrode materials for SIBs and PIBs via in situ TEM is summarized. First, the importance of in situ TEM is highlighted. Then, based on the three types of electrochemical reaction, i.e., intercalation reaction, conversion reaction and alloying reaction, the structural evolution and reaction kinetics at atomic resolution, and their relation to the electrochemical performance of electrode materials are reviewed and described in detail. Finally, future directions of in situ TEM for SIBs and PIBs are proposed. Therefore, the in‐depth understanding revealed by in situ TEM will give an instructive guide in rational design of electrode materials for high performance electrode materials of SIBs and PIBs. Graphical abstract: In situ transmission electron microscopy (TEM) is one of the most noteworthy techniques to understand and monitor electrochemical processes at an atomic scale with real‐time imaging. The current progress in unraveling reaction mechanisms of electrode materials for sodium potassium ion batteries via in situ TEM is summarized. The in‐depth understanding revealed by in situ TEM will give an instructive guide in rational design of electrode materials for high performance electrode materials of sodium ion and potassium ion batteries.